ADSORPSI ION LOGAM Fe DALAM LIMBAH TEKSTIL SINTESIS DENGAN MENGGUNAKAN METODE BATCH - Karim, Muhammad Arief; Juniar, Heni; Ambarsari, M. Fitria Putri (Jurnal Distilasi, 2017)
Adsorption is a process occurs in a fluid, either it is liquid or gas, bonded in a solid or liquid (absorbent agent, adsorbent) and eventually creates a thin layer or film (adsorbed agent, adsorbent) on its surface. In this study, the writer did the process of the adsorption of Fe metal ion to the adsorbent of carbide waste that has been processed into tablet with 3x5 mm size, adsorption was done with Batch process by stirring 15gr or adsorbent into 100ml of synthetic waste with 50rpm stirring speed. There are two factors that influence the decrease of Fe metal concentration in synthesis waste which is the influence of pH and time. This study used variables of adsorption time (1; 2; 3; 4; 5; 6) hours with pH (2.5; 4.1) for each hour with an initial concentration of Fe 800g metal ions. This study was conducted to obtain the optimum value of pH and concentration of final Fe metal ions with the comparison of initial pH ratio and predetermined time. Seen from the matrix results of the study, it can be concluded that the longer the stirring time the more metal ions are absorbed by the adsorbent of carbide waste and pH value also rises.